Clinical pseudomonas aeruginosa: potential factors of pathogenicity and resistance to antimicrobials - Hostacká, A; Ciznár, I; Slobodníkova, L; Kotulová, D (Folia microbiologica, 2006)
Resistance to 17 antimicrobials, surface hydrophobicity, motility, biofilm, production of N-acylhomoserine lactone signal molecules (N-butyrylhomoserine lactone and N-3-oxolauroylhomoserine lactone) and response to oxidative stress were analyzed in 47 clinical Pseudomonas aeruginosa strains. In addition to natural resistance, the strains demonstrated the greatest level of resistance to cefotaxime (91.5%). Isolates in the range of 44.7-57.4% were resistant to aminoglycosides and ciprofloxacin, of 25.5-36.2% to cephalosporins. On the other hand, 97.9% remained susceptible to meropenem, 93.6% to piperacillin + tazobactam and 87.2% to piperacillin. The majority of the strains (72.3%) manifested their hydrophilic character. Higher zones of motility showed 12 isolates (in average 54.8 mm) as compared to the others (30.2 mm). Approximately 1/3 of the strains (29.8%) produced a higher amount of biofilm quantified by measuring the absorbance of solubilized crystal violet (0.20-0.46) than the rest of isolates (0-0.19). All but two strains produced N-3-oxolauroylhomoserine lactone and in 48.9% of samples N-butyrylhomoserine lactone were detected. Only four isolates with higher biofilm production showed both types of homoserine lactone. Majority of the strains (70.2%) manifested higher resistance to H2O2 than the rest of the strains. The group of strains resistant to aminoglycosides and ciprofloxacin revealed a significantly higher number of hydrophobic strains (compared with the sensitive ones). In contrast, higher number of strains sensitive to aminoglycosides and ciprofloxacin or only to ciprofloxacin produced N-butyrylhomoserine lactone and biofilm (compared to the resistant ones). Such association was not found among the rest of the tested parameters. The results indicate that the resistance to antimicrobials in P. aeruginosa isolates was not generally associated with changes in the production of the pathogenicity factors.
Keywords: Hydrophobic and Hydrophilic Interactions; oxidační stres; pseudomonádové infekce; fenotyp; Phenotype; gama-butyrolakton; hydrofobní a hydrofilní interakce; virulence; Drug Resistance, Bacterial; Adaptation, Physiological; antibakteriální látky; pohyb; Oxidants; Pseudomonas Infections; peroxid vodíku; fyziologická adaptace; Virulence; Hydrogen Peroxide; lidé; Pseudomonas aeruginosa; Anti-Bacterial Agents; Biofilms; Humans; bakteriální léková rezistence; Movement; genciánová violeť; Gentian Violet; biofilmy; 4-Butyrolactone; Oxidative Stress; oxidancia